Biennial harvest reduces rhizome multiplication rate and provides no yield advantage in ginger (Zingiber officinale Roscoe.) - Sasikumar, K Kandiannan, D Prasath, B (Journal of Spices and Aromatic Crops, 2016)
A study was conducted during 2009–10 and 2010–11 under rainfed condition to observe the sprout emergence, tiller production and yield when the ginger was allowed to grow in the second season/year without harvest in first year/season. First generation ginger was not harvested and allowed to emerge on the same container and harvested in subsequent year in second generation in the month of January 2011. After harvesting, fresh rhizome was cleaned and sorted into first year produce and second year produce based on their appearance and texture and weighed separately, their proportion was estimated and multiplication rate from first generation crop to second generation crop was calculated. The mean shoot emergence and tiller production were five and 19, respectively. Average yield in first, second years and total yield were 209, 566 and 775 g plant-1, respectively. The share between first and second year yield were 27.8 and 72.2%, respectively and mean multiplication rate was 3.5 times. Although, yield levels tend to increase in second season, the multiplication rate was much reduced. Hence, the practice of biennial harvest may not have clear yield advantage over regular annual harvest.